Decolonizing management and organization studies : why, how, and what (Research in the sociology of organizations ;, 2025)
The ebook edition of this title is Open Access and freely available to read online. Discussions on decolonizing management and organization studies have gained attention. This volume of Research in the Sociology of Organizations paves the way forward on what scholars from management and organization studies can or should not do to decolonize their discipline. How can we create a community sensitive to integrating diverse voices and perspectives that provide opportunities to diversify knowledge creation? Acknowledging that knowledge creation requires diversification to establish impactful insights able to tackle the Sustainable Development Goals beyond the Western world, this collection further develops the literature that is needed to build measures for decolonized management and organization studies. Divided into five sections, Section A aims to take stock of existing debates on decolonizing management and organization studies and build directions for future research. In section B, authors of different expertise address the need and, therefore, the why for decolonizing management studies from various angles. Section C discusses the how questions and tries to elaborate on ideas and empirical examples to decolonize the discipline. In section D, the authors tackle and reflect on what needs to be fundamentally changed to allow the diversification of knowledge creation. Concluding with reflections from prominent and young scholars of the discipline, Decolonizing Management and Organization Studies informs management organizational studies theory and contributes new insights for the academic community.